2011 IEEE International Conference on Robotics and Automation 2011
DOI: 10.1109/icra.2011.5980459
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance based control of a robotic manipulator for interventions in the beating heart

Abstract: As a part of an ongoing project, in this paper we introduce the first version of a system which has a novel methodology for Cine (as in cinema) MRI based control of a cardiac robot for beating heart surgeries. The system uses the preoperative planning approach that we developed earlier, and integrates it to the intraoperative algorithms for controlling a robot and tracking some specific landmarks of a highly dynamical surgical field. In particular, our late studies presented herein aim to demonstrate the feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This system is the result of prior work focused on the development an d integration of enabling methodologies in MRI-guided and robot-assisted intracardiac procedures [14,18]. Studies with collaborating clinicians clearly demonstrated that the human-machine interface could be substantially improved in terms of intuitiveness and ergonomics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This system is the result of prior work focused on the development an d integration of enabling methodologies in MRI-guided and robot-assisted intracardiac procedures [14,18]. Studies with collaborating clinicians clearly demonstrated that the human-machine interface could be substantially improved in terms of intuitiveness and ergonomics.…”
Section: Discussionmentioning
confidence: 99%
“…1(a) illustrates a model of a generalized slave manipulator which consists of a straight tubular link with a bending section near its distal tip. This manipulator was derived in prior TAVI simulation studies [18] to be suitable for intracardiac procedures via a transapical access . Although the master device is designed for the TAVI slave manipulator, the principles used for this design are appropriate for other fixed-point access procedures with remote center of motion.…”
Section: A Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the same line, Yeniaras et al . proposed the application of real‐time MR images to control a robot for intracardiac beating‐heart surgery. They used offline cine‐MRI images and a simulated robot to prove the concept of visual servoing by tracking tool and tissue in transapical cardiac interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it requires deliberate design consideration that minimizes the H. Su transverse space of the closed-bore. To comply with this restriction, a number of mechanisms have been investigated: (i) remote center of motion (RCM) mechanism using arch structure [1] and parallelogram, (ii) articulated serial linkage mechanism [2] and a more generic modular approach [3], (iii) a 5-DOF parallel manipulator [4], (iv) compliant mechanism, including bending mechanism of micro grasping forceps for neurosurgery [5] and leverage and parallelepiped mechanism for micro surgery [6], (v) continuum type robot utilizing steerable needles [7] and (vi) a wire-driven needle angulation mechanism [8].…”
Section: A Mechanisms For Mri-guided Surgical Interventionsmentioning
confidence: 99%